1985
DOI: 10.1148/radiology.155.1.3975389
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of cerebral infarction along the distribution of the basal perforating arteries. Part II: Thalamic arterial group.

Abstract: Computed tomographic (CT) manifestations of cerebral infarction along the distribution of the basal perforating arteries were reviewed and correlated with cerebral angiography. Infarcts in the territories of perforators were demonstrated individually based on knowledge of their three-dimensional distribution as shown by microangiography of cadavers. In Part II of the study, the posterior areas supplied by the thalamic arteries were examined. Infarcts in the area supplied by the thalamotuberal arteries involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Other smaller studies have demonstrated the AOP ischemic pattern in 2% of all ischemic strokes 24 and from 4% to 18% of all thalamic strokes. 4,9,19,24,25 The AOP is rarely visualized with conventional angiography, and to our knowledge, only 3 other authors have successfully demonstrated this variant. 18,26,27 We were able to capture a striking image of the AOP with conventional angiography in 1 of our patients (Fig 6).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Other smaller studies have demonstrated the AOP ischemic pattern in 2% of all ischemic strokes 24 and from 4% to 18% of all thalamic strokes. 4,9,19,24,25 The AOP is rarely visualized with conventional angiography, and to our knowledge, only 3 other authors have successfully demonstrated this variant. 18,26,27 We were able to capture a striking image of the AOP with conventional angiography in 1 of our patients (Fig 6).…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8] The paramedian arteries have great variability with respect to number, size, and territorial contribution to the thalamus. 1,2,6,[9][10][11][12][13] Many authors have demonstrated that the paramedian arteries can supply both the paramedian and the anterior thalamic territories, especially when the polar artery is absent. 1,4,6,9,10,[14][15][16][17][18][19] The variable presence of the polar artery (absent in 30%-60% of the population) 7,15,16 is not surprising because it arises from the PcomA, which itself is highly variable and can be absent or hypoplastic.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The low incidence of lower extremity-dominant motor dysfunction may reflect the supply of the posterior part of the corona radiata by the perforating arteries from the posterior communicating artery, whereas the anterior part is supplied by the lenticulostriate arteries. 9, 40) Our patients with corticospinal tract injury in the middle one third showed little recovery in the upper extremity but marked recovery in the lower extremity at follow up, indicating that the middle one third of the corticospinal tract at the level of the corona radiata is strongly correlated with upper extremity motor function. Similarly, our findings also suggest that the posterior one third of the corticospinal tract is involved in lower extremity motor function.…”
Section: Discussionmentioning
confidence: 63%